Chasing Automation : The Politics of Technology and Jobs from the Roaring Twenties to the Great Society - Prout, Jerry (Book collections on Project MUSE., 2022)
"Chasing Automation describes how in the period from 1921 to 1966, despite the inherent limitations of politics to anticipate the effects of technology on jobs, an eclectic and fragile coalition of reform-minded politicians successfully erected a legal framework that mitigated the worst effects of technological unemployment"--